Evaluation of Mesh Infection in Patient with Laparoscopic Inguinal Hernia Repair: A Retrospective Study - Kanwal, Sidra Fatima Afzal, Ajmal Khan Bazai, Sorath Bukhari, Abdul Latif, Shah Nawaz Khatti (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate Post-Laparoscopic infection in Mesh followed by inguinal hernia repair. Study design: A retrospective study Place and Duration: This study was conducted at Jinnah Postgraduate and Medical Centre Karachi from April 2021 to April 2022 Methodology: A total of 80 participants were included in the study. All the patients had an extensive infection in the mesh followed by mesh hernia repair through laparoscopy. The preoperative workup was done for all the patients before a laparoscopic excision of mesh. A drain was placed in the preperitoneal space after the removal of the mesh. Closure of the peritoneal flap was done after that with a 3/0 absorbable suture. Result: The course of the operation was uneventful for all the patients. Only two patients required a sigmoidectomy for the repair of the fistula. Three patients presented with contralateral side infection and mesh residues around the pubic. A second laparoscopy was done on those three patients. Recurrence of hernia was seen in four of the cases observed on follow-up. Conclusion: Laparoscopic removal of the mesh is a superior approach to the open surgical removal of the mesh for the treatment of mesh infection. However, prevention of infection by prophylactic antibiotics, maintaining an aseptic environment during hernia repair surgery, and proper sterilization of the instruments can prevent the infection. Keywords: laparoscopic, mesh infection, inguinal hernia repair